Performance of Pediatric Mortality Prediction Scores for PICU Mortality and 90-Day Mortality*. Issue 2 (February 2019) - Jacobs, An; Flechet, Marine; Vanhorebeek, Ilse; Verstraete, Sören; Ingels, Catherine; Casaer, Michael P.; Soto-Campos, Gerardo; Verbruggen, Sascha C.; Joosten, Koen F.; Güiza, Fabian; Van den Berghe, Greet
Abstract : Objectives: The use of mortality prediction scores in clinical trials in the PICU is essential for comparing patient groups. Because of the decline in PICU mortality over the last decades, leading to a shift toward later deaths, recent trials use 90-day mortality as primary outcome for estimating mortality and survival more accurately. This study assessed and compared the performance of two frequently used PICU mortality prediction scores for prediction of PICU and 90-day mortality. Design: This secondary analysis of the randomized controlled Early versus Late Parenteral Nutrition in the Pediatric Intensive Care Unit trial compared the discrimination (area under the receiver operating characteristic curve) and calibration of the Pediatric Index of Mortality 3 and the Pediatric Risk of Mortality III scores for prediction of PICU and 90-day mortality. Setting: Three participating PICUs within academic hospitals in Belgium, the Netherlands, and Canada. Patients: One-thousand four-hundred twenty-eight critically ill patients 0–17 years old. Interventions: None. Measurements and Main Results: Although Pediatric Index of Mortality 3 only includes information available at the time of PICU admission, thus before any intervention in the PICU, it showed good discrimination (area under the receiver operating characteristic curve, 0.894; 95% CI, 0.892–0.896) and good calibration (no deviation from the diagonal, p = 0.58) for PICU mortality. Pediatric Risk of Mortality III, which involves the worst values for the evaluated variables during the first 24 hours of PICU stay, was statistically more discriminant (area under the receiver operating characteristic curve, 0.920; 95% CI, 0.918–0.921; p = 0.04) but poor in calibration (significant deviation from the diagonal; p = 0.04). Pediatric Index of Mortality 3 and Pediatric Risk of Mortality III discriminated equally well between 90-day mortality and survival (area under the receiver operating characteristic curve, 0.867; 95% CI, 0.866–0.869 and area under the receiver operating characteristic curve, 0.882; 95% CI, 0.880–0.884, respectively, p = 0.77), but Pediatric Risk of Mortality III was not well calibrated ( p = 0.04), unlike Pediatric Index of Mortality 3 ( p = 0.34). Conclusions: Pediatric Index of Mortality 3 performed better in calibration for predicting PICU and 90-day mortality than Pediatric Risk of Mortality III and is not influenced by intervention or PICU quality of care. Therefore, Pediatric Index of Mortality 3 seems a better choice for use in clinical trials with 90-day mortality as primary outcome.